Human N-acetyltransferase 2 (NAT2) gene variability in Brazilian populations from different geographical areas - Lopes, Márcia Quinhones P.; Teixeira, Raquel Lima F.; Cabello, Pedro Hernan; Nery, José Augusto C.; Sales, Anna Maria; Nahn J. R., Edilbert Pellegrini; Moreira, Marilda Vieira; Stahlke, Ewalda Von Rosen; Possuelo, Lia Gonçalves; Rossetti, Maria Lucia R.; Rabahi, Marcelo F.; Silva, Luciana F. M.; et al. (Frontiers in Pharmacology, 2023)
We describe the genetic variability of human N-acetyltransferase 2 (NAT2) gene and the predominant genotype-deduced acetylation profiles of Brazilians from five geographical regions. A total of 964 individuals were genotyped for NAT2 by sequencing the entire coding exon. Twenty-three previously described NAT2 single nucleotide polymorphisms (SNPs) were identified, including the seven most common ones globally (c.191G>A, c.282C>T, c.341T>C, c.481C>T, c.590G>A, c.803A>G and c.857G>A). The main allelic groups were NAT2*5 (36%) and NAT2*6 (18.2%), followed to the reference allele NAT2*4 (20.4%). Combined into genotypes, the most prevalent allelic groups were NAT2*5/*5 (14.6%), NAT2*5/*6 (11.9%) and NAT2*6/*6 (6.2%). The genotype deduced NAT2 slow acetylation phenotype was predominant but showed significant variability between geographical regions. The prevalence of slow acetylation phenotype was higher in the Northeast, North and Midwest (51.3%, 45.5% and 41.5%, respectively) of the country. In the Southeast, the intermediate acetylation phenotype was the most prevalent (40.3%) and, in the South, the prevalence of rapid acetylation phenotype was significantly higher (36.7%), when compared to other Brazilian states (p<0.0001). Comparison of the predicted acetylation profile among regions showed homogeneity among the North and Northeast but was significantly different when compared to the Southeast (p=0.0396). The Southern region was significantly different from all other regions (p<0.0001). This study contributes not only to current knowledge of the NAT2 population genetic diversity in different geographical regions of Brazil, but also to the reconstruction of a more accurate phenotypic picture of NAT2 acetylator profiles in those regions.